Reconstructing the flipped classroom method. Its place in the context of scientific theory and 21st century educational challenges - Magdalena Kolber (Edukacja Ustawiczna Dorosłych)
The aim of the article is to discuss the flipped learning-FL method. The research problem focuses on finding answers to the following questions: which scientific theories provide the theoretical framework for this method? Why is FL a teaching approach for the 21st century? The research method is a critical literature review. An analysis through the lens of constructivism and B. Bloom’s Taxonomy of Educational Objectives reveals that the method develops higher-order thinking skills and learner’s autonomy. The approach places educators in the role of facilitators and guides, shifting the learners to the centre of the educational process. In addition, the method can be successfully applied to bilingual as well as distance education.